Hubungan Komunikasi Keluarga dengan Kecenderungan Penggunaan Strategi Coping pada siswa - Della Agustia Ningsih; Diah Utaminingsih; Moch Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem of this research is the use of negative coping strategy in students. The aim of this research is correlation of Family Communication with the trends of the use of strategy Coping of the eleventh grade students at Senior High School 1 Gadingrejo Academic Year 2019/2020. Descriptive Correlational method was applied to this research with the population of this research was 374 students. Data Collecting technique of this research used family communication pattern withstrategy coping. The data analysis technique of the research used product moment Corelation. The results of this research were gained so r hitung 0.791 ˃ r tabel 0.133 with significance level of 0.05%, meaning that thre is a significant positive correlationof family communication with the trends of the use of strategy coping, the higher the consensual family communication, the higher the tendency of using coping strategy to focus on the problem, and vice versa, the lower the consensual family communication, the lower the tendency to use coping strategy to focus on the problem.Permasalahan dalam penelitian ini adalah kecenderungan penggunaan strategi copingnegatif pada siswa. Tujuan penelitian ini untuk mengetahui hubungan antara komunikasi keluarga dengan kecenderungan penggunaan strategi copingpada siswa kelas XI SMA Negeri 1 Gadingrejo Tahun Ajaran. 2019/2020. Penelitian ini merupakan penelitian korelasional. Populasi penelitian ini berjumlah 374 siswa. Teknik pengumpulan data menggunakan skala pola komunikasi keluarga dan strategi coping. Teknik analisis data menggunakan korelasi product moment. Hasil penelitian diperoleh yaitu r hitung 0.791 ˃ r tabel 0.133 dengan taraf signifikansi 0.05%, artinya terdapat hubungan positive yang signifikan antara komunikasi keluarga dan kecenderungan penggunaan strategi coping. Semakin tinggi komunikasi keluarga konsensual maka tingkat kecenderungan penggunaan strategi coping berfokus pada masalah semakin tinggi begitu juga sebaliknya, semakin rendah komunikasi keluarga konsensual maka kecenderungan penggunaan strategi coping berfokus pada masalah semakin rendah.Kata kunci: hubungan, komunikasi keluarga, strategi coping